O uso produtivo do se reflexivo na fala de João Pessoa: uma abordagem funcionalista. - Mello, Fernanda Rosário de (2005)
Structures in Portuguese using se particles have several ways to be analyzed. Among them, we may emphasize those ones which present the refexive ´se ` pronoun. Using oral (con)texts collected from the Projeto Variação Lingüística do Estado da Paraíba (VALPB), this research aims to study the functional behavior of the 3ª person clitic in reflexive structures. The development of this research took into account social and linguistic factors, using as theoretical support the basic principles of the American Functionalism. In this research, we can realize the reflexive se pronoum expanding its use in the João Pessoa speech. This element loses certain features that are esencial for to be characterized like a reflexive one, in certain way that its going to expanding its occurrence context, becomming more obscure, less transparent in its function. It starts to be used ina context more abstract, leaving its main function and taking new aspects in the speech.